Doctor Draft Substitute : hearings before the United States Senate Committee on Armed Services, Eighty-Fifth Congress, first session, on June 6, 1957. - United States. Congress. Senate. Committee on Armed Services (Washington : U.S. G.P.O., 1957)
Considers (85) H.R. 6548.
Considers legislation to authorize special military induction of physicians, dentists, and allied health personnel.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VI
Mode of access: Internet.
Keywords: Draft -- Law and legislation -- United States; United States -- Armed Forces -- Officers; United States -- Armed Forces -- Medical care